Pyrimidine Synthesis in Neurospora crassa: Regulation of Enzyme Activities - Caroline, Dina F. (1969)
The regulation of several enzymes involved in pyrimidine biosynthesis in Neurospora crassa has been studied. Elevation of ATCase (l-aspartate carbamoyltransferase) activity is found in all pyrimidine-requiring mutants when they are starved for uridine. DHOase (dihydroorotase) is an unstable enzyme, and it is impossible to conclude what type of regulation, if any, controls this enzyme. DHOdehase (dihydroorotate dehydrogenase) activity shows a marked elevation in uridine-starved pyr-2 cultures, a mutant blocked late in the pathway. Several mutants blocked early in the pathway show much smaller increases in DHOdehase activity and possible explanations for this are discussed. Differences in the modes of regulation of the pyrimidine biosynthetic pathways in various organisms are compared.